THE EFFECT OF DIGESTATE AND WOOD ASH MIXTURES ON THE PRODUCTIVITY AND YIELD QUALITY OF WINTER WEAT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Field trials were conducted at the Study and Research Farm “Peterlauki” (56°53' N, 23°71' E) of the Latvia University of Life Sciences and Technologies. Soil characteristics: sod-stagnogley soil; granulometric composition – heavy dusty sand clay. Soil agrochemical parameters: pH KCl 6.7; organic matter content – 26 g kg-1; phosphorus content – 60 mg kg-1 P2O5; and potassium content – 144 mg kg-1 K2O. Winter wheat sowings were established using different variants of a fertilizer mix with cattle (from JSC “Ziedi JP”) manure digestate (D) and wood ash (P) (from LLC “Gren Jelgava”) in different ratios. The norms of the innovative mixed fertilizer for cattle manure digestate and wood ash were 5, 10, and 20 t ha-1. Unfertilized winter wheat plots were used as control. Variants in the two-factor trial were randomized in triplicate. In the experiment, the influence of the researched factors on winter wheat grain yield, the content of starch and protein in grains, grain volumetric weight (kg hL-1), and the mass of 1000 grains were determined. The aim of the study was to determine the impact of biogas fermentation by-product (digestate) and cogeneration plant and boiler house residues (wood ash) on the yield and quality of winter wheat. Depending on the study variant, the winter wheat yield varied from 4.26 to 9.03 t ha-1. It was established that the average winter wheat grain yield in the control variant was 5.29 t ha-1, which is significantly (p<0.05) lower (5.94 t ha-1) than in the variants using fertilizers of digestate and wood ash mixtures. Using digestate and wood ash mixtures, sufficiently high and high-quality winter wheat yields can be obtained without the use of mineral fertilizers. The mixtures of digestate and wood ash are an innovative fertilizer way for improving the soil fertility, which is also suitable for winter wheat.